Melatonin signalling in Schwann cells during neuroregeneration - Klymenko, Andrii; Lutz, David (Frontiers in Cell and Developmental Biology, 2022)
It has widely been thought that in the process of nerve regeneration Schwann cells populate the injury site with myelinating, non–myelinating, phagocytic, repair, and mesenchyme–like phenotypes. It is now clear that the Schwann cells modify their shape and basal lamina as to accommodate re–growing axons, at the same time clear myelin debris generated upon injury, and regulate expression of extracellular matrix proteins at and around the lesion site. Such a remarkable plasticity may follow an intrinsic functional rhythm or a systemic circadian clock matching the demands of accurate timing and precision of signalling cascades in the regenerating nervous system. Schwann cells react to changes in the external circadian clock clues and to the Zeitgeber hormone melatonin by altering their plasticity. This raises the question of whether melatonin regulates Schwann cell activity during neurorepair and if circadian control and rhythmicity of Schwann cell functions are vital aspects of neuroregeneration. Here, we have focused on different schools of thought and emerging concepts of melatonin–mediated signalling in Schwann cells underlying peripheral nerve regeneration and discuss circadian rhythmicity as a possible component of neurorepair.